2004
DOI: 10.1242/jcs.01579
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of 3-phosphoinositide dynamics duringDictyosteliumphagocytosis and chemotaxis

Abstract: Phagocytosis and chemotaxis are receptor-mediated processes that require extensive rearrangements of the actin cytoskeleton, and are controlled by lipid second messengers such as phosphatidylinositol 3,4,5-trisphosphate [PtdIns(3,4,5)P3] and phosphatidylinositol 3,4-bisphosphate [PtdIns(3,4)P2]. We used a panel of pleckstrin homology (PH) domains with distinct binding specificities for PtdIns(3,4,5)P3 and PtdIns(3,4)P2 to study the spatiotemporal dynamics of these phosphoinositides in vivo. During phagocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
129
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 46 publications
16
129
1
1
Order By: Relevance
“…18 This probe displayed no difference in labeling of the inner and external areas, or the waves separating them, indicating that PI (3,4,5)P3 is the phosphoinositide that distinguishes these two areas in wave-forming cells. When the waves propagate in one or the other direction, the inner and external areas undergo reciprocal changes in size with negligible changes in the total area of the substrate-attached Figure 4.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…18 This probe displayed no difference in labeling of the inner and external areas, or the waves separating them, indicating that PI (3,4,5)P3 is the phosphoinositide that distinguishes these two areas in wave-forming cells. When the waves propagate in one or the other direction, the inner and external areas undergo reciprocal changes in size with negligible changes in the total area of the substrate-attached Figure 4.…”
Section: Resultsmentioning
confidence: 95%
“…10,23 Figure 1A The domain of CRAC, a cytosolic regulator of adenylyl cyclase in Dictyostelium, 17 binds with high specificity to PIP3 and PI(3,4) P2. 16,18 Thus, PHcrac-GFP, a fusion of GFP to the PH domain of CRAC, labels the membrane of forming phagosomes and disappears shortly after the phagosome seals. [18][19][20] Using PHcrac-GFP together with mRFP-LimE∆, a probe for filamentous actin, 21 we examined cells in the process of generating actin waves on a planar surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the concentration of various phosphoinositides changes during phagosome formation and the following maturation (35,64,65). In mammalian cells, the relative abundance of PIP45 is slightly higher at the nascent phagosome, whereas the level of PIP345 increases at the early phagosome, presumably followed by a rise in PIP35 at the later stages (35).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these asymmetries are conserved in migratory cells, such as Dictyostelium discoideum, mammalian leukocytes, fibroblasts, and axonal growth cones (2)(3)(4)(5)(6). In addition, these signaling molecules display characteristic localization patterns that are important for the regulation of other cellular behaviors, such as cytokinesis and phagocytosis, as well as in nonmigratory cells, such as epithelia (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%